Dose and time dependent cytotoxicity of Blepharis maderaspatensis (L) against various human cancer cell lines - Bhutkar Pratima Milind; V. Suganthi; Bhutkar Milind Vishnu (Al Ameen Journal of Medical Sciences)
Background: Traditionally, Blepharis maderaspatensis has been assigned antioxidant, anti-inflammatory, antimicrobial, and wound healing properties. Aim and Objectives: Present study was aimed to assess dose and time-dependent cytotoxic potential of B. maderaspatensis. Material and Methods: This was an experimental study with positive and negative control under standard laboratory conditions. In vitro cytotoxic activity of ethanolic extract of B. maderaspatensis was assessed by MTT assay on MCF7, PA1, HT29, A375, HepG2 cancer cell lines. All the cell lines were treated with increasing concentration of the extract for 24, 48 and 72 hours or standard anticancer drug. IC50 value was calculated for each duration from sigmoid dose-response curve by using GraphPad Prism8 software. Results: Ethanolic extract of B. maderaspatensis was effective cytotoxic agent against all the tested cancer cell lines in dose and time-dependent manner. Cytotoxicity was maximum against A375 (melanoma) (IC50: 21.46μg/ml), followed by HT29 (colon cancer) cell lines (IC50: 32.66μg/ml). For all other cell lines IC50 values were >100μg/ml. Conclusions: Ethanolic extract of B. maderaspatensis is effective cytotoxic agent and can be evaluated further to study its mechanism of action. Investigations involving purification, identification of active principles and determination of mechanisms of action can be helpful in drug discovery program.